Synthesis, structure and thermal properties of montmorillonite/ionic liquid ionogels. Issue 57 (21st September 2020) - Noskov, Andrew V.; Alekseeva, Olga V.; Shibaeva, Valeriya D.; Agafonov, Alexander V.
Abstract : Sodium montmorillonite (Na-MMT) was synthesized as a result of two-stage processing of natural bentonite (Bent), and its particle-size distribution, structure and morphology were studied. Abstract : Sodium montmorillonite (Na-MMT) was synthesized as a result of two-stage processing of natural bentonite (Bent), and its particle-size distribution, structure and morphology were studied. It was found that the two-stage processing of the original clay resulted in a significant increase in the specific surface area (from 72 to 120 m 2 g −1 ). The prepared Na-MMT powder was modified by two ionic liquids (ILs), namely, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMImNTf2 ) and 1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide (BMImNTf2 ). Several methods, such as SEM, XRD, TG, DSC, FTIR spectroscopy were used to study the structure and thermal behavior of the produced ionogels. The effects of the IL cation on thermal characteristics of the Na-MMT/IL ionogels were studied. Using the DSC, characteristic temperatures of glass transition, crystallization and melting were determined for Na-MMT/IL composites. Taking into account the literature data and using the method of thermogravimetric analysis, it was shown that ionogel formation was accompanied by a decrease in the thermal stability of the IL.